Relationship of Physical Culture with Other Directions - Nurmatov Farkhat Abdualimovich (International Journal on Human-Computing Studies, 2021)
Physically adequate development facilitated normal mental development. Chernyshevsky's views on the relationship of mental and physical processes of dialectical materialism to mental and physical activity are reflected in his works: "Any labor is a mental, physical person. in the second, the muscles o The work of the brain was carried out through the interaction of the muscles, the activity of the muscles, and the control of the brain